THE INFLUENCE OF MOBILE MARKETING ON CONSUMER BEHAVIOR IN EMERGING MARKETS - Budi Raharja , Arif (KRIEZ ACADEMY : Journal of development and community service, 2025)
Background:Mobile marketing has emerged as a transformative force in consumer engagement, particularly in emerging markets where smartphone adoption and digital connectivity are rapidly increasing. Mobile platforms serve as essential channels for businesses to reach diverse audiences, offering personalized and contextually relevant experiences. Despite its potential, mobile marketing faces challenges such as connectivity issues, digital literacy gaps, and privacy concerns. Aims:This study aims to explore the impact of mobile marketing on consumer behavior in emerging markets. It investigates the drivers of mobile commerce adoption, examines the challenges businesses face, and evaluates the long-term effects of mobile marketing on brand loyalty and advocacy. The goal is to provide actionable insights for optimizing mobile marketing strategies. Research Method:A mixed-methods approach was employed, combining quantitative surveys of 500 respondents with qualitative interviews of 40 participants across emerging markets. Statistical tools were used to analyze trends, while thematic analysis uncovered deeper insights into consumer preferences and challenges. Results and Conclusion:The findings reveal that 64% of respondents make at least one monthly purchase via mobile devices, with convenience, secure payment options, and user-friendly interfaces as key drivers. Social media platforms, particularly Facebook, Instagram, and TikTok, play a significant role in shaping consumer behavior, with 78% of respondents discovering products through these channels. Challenges such as poor internet access, digital literacy gaps, and privacy concerns remain barriers to maximizing mobile marketing’s potential. Addressing these challenges through infrastructure investment, education, and transparent data practices can unlock significant opportunities. Long-term effects include increased brand loyalty (65%) and advocacy (62%), highlighting the transformative potential of mobile marketing in fostering enduring consumer relationships. Contribution:This study provides a comprehensive framework for understanding the dynamics of mobile marketing in emerging markets, offering practical recommendations for businesses to refine their strategies. It bridges the gap between theoretical concepts and real-world applications, contributing to the broader discourse on digital marketing and economic inclusion.